Bronchial thermoplasty in severe asthma in Australia. Issue 5 (May 2017) - Langton, David; Sha, Joy; Ing, Alvin; Fielding, David; Wood, Erica
Abstract : Background: Bronchial thermoplasty (BT) is an approved bronchoscopic intervention for the treatment of severe asthma. However, limited published experience exists outside of clinical trials regarding patient selection and outcomes achieved. Aims: To evaluate the effectiveness and safety of BT in patients with severe asthma encountered in clinical practice. Methods: This is a retrospective analysis of the first 'real world' data from Australia. The following outcomes were measured prior to, and 6 months following BT: spirometry, Asthma Control Questionnaire‐5 (ACQ‐5) score, reliever and preventer medication use and exacerbation history. Results: Twenty patients were treated from June 2014 to December 2015 at three university teaching hospitals. All subjects met the European Respiratory Society/American Thoracic Society definition of severe asthma. Mean pre‐bronchodilator forced expiratory volume in 1 s was 62.8 ± 16.6% predicted (range: 33–95%). All patients were being treated with high dose inhaled corticosteroids, long‐acting beta2 agonists and long‐acting muscarinic antagonists. Ten patients (50%) were taking maintenance oral prednisolone. Most subjects also required at least one of montelukast (65%), omalizumab (30%) and methotrexate (20%). ACQ‐5 improved from 3.6 ± 1.1 at baseline to 1.6 ± 1.2 at 6 months, P  < 0.001. Short‐acting reliever use decreased from a median of 8.0–0.25 puffs/day, P  < 0.001, and exacerbations requiring corticosteroids also significantly reduced. Five of 10 patients completely discontinued maintenance oral corticosteroids. Ten patients with a baseline forced expiratory volume in 1 s of <60% predicted significantly improved from 49.2 ± 9.6% to 61.8 ± 17.6%, P  < 0.05. Only two procedures required hospitalisation beyond the planned overnight admission. Conclusion: BT is a safe procedure which can achieve clinical improvement in those with uncontrolled symptoms and severe airflow obstruction.